ANALISIS PREDIKSI PENJUALAN IKLAN MEDIA MASA DAN ELEKTRONIK MENGGUNAKAN METODE LINEAR REGRESSION - Adham Novalas Putra Wibisono; Nuril Lutvi Azizah; Yunianita Rahmawati (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Technology continues to evolve rapidly, especially in the field of data analysis. Advertising sales in print and electronic media are one of the main strategies to achieve profits. In the context of today's era, successful ad sales require accurate and valid data. Linear Regression (LR) is a data analysis technique that predicts the value of unknown data by using other related and known data values. Mathematically model unknown or dependent variables and known or independent variables as linear equations. The research "Analysis of Prediction of Mass and Electronic Media Advertising Sales Using the Linear Regression Method" will be improved so that it can be used to facilitate the evaluation process and profits on the sale of mass and electronic media advertisements. The author will develop an analysis of advertising sales in mass and electronic media using the linear regression method.